Pyloric Balloon Dilatation for Delayed Gastric Emptying in Children. (1st November 2001) - Israel, DM; Mahdi, G; Hassall, E
Abstract : Delayed gastric emptying may manifest with symptoms of epigastric pain, early satiety and delayed vomiting, and at times may be associated with failure to thrive. These symptoms and signs may improve following surgical pyloroplasty. To determine whether pyloric balloon dilation (PBD) is an effective therapy for children with these symptoms, hospital records of all children who underwent endoscopic PBD between October 1991 and March 1994 at British Columbia's Children's Hospital were reviewed. Excluded were children with chromosomal abnormalities, neurological disorders and erosive esophagitis. Through-the-scope balloons of diameter 15 or 18 mm were positioned in the pyloric channel and inflated with air to 2334 or 1815 mmHg respectively, for 2 min. Nineteen children with a mean age of 3.75 years (range eight months to 10 years) who presented with symptoms for more than three months (mean 11 months) were identified. Eleven children presented with failure to thrive, 14 with delayed vomiting and 10 with early satiety. Results of gastric emptying tests at 90 min ranged from 8% to 75% (mean 32%). The pylorus was difficult to intubate in 11 of 19 children, and in two the pylorus could not be passed before PBD. No complications were experienced with PBD. Thirteen children had complete resolution of symptoms, and five had transient improvement lasting four to eight weeks after PBD with subsequent complete resolution of symptoms following surgical pyloroplasty. One child continued to have mild symptoms after PBD but did not have further treatment. This study suggests that PBD is a safe and effective therapeutic option in children with symptoms and signs associated with delayed gastric emptying.